Poverty Analysis in Agricultural Water Operations of the World Bank - Darghouth, Salah; Ward, Christopher; Gittinger, Price; Roux, Julienne; Srivastava, Animesh (World Bank, Washington, DC, 2012)
Agricultural water has been seen as a prime mechanism for fostering rural economic growth and reducing rural poverty. But agricultural water has encountered problems of performance, profitability and sustainability. This resulted in a reduction in investments from governments and lending from development organizations like the World Bank up to early 2000s. A sourcebook on improving poverty reduction performance of agricultural water investments should be prepared to help task teams assess the poverty reduction role of agricultural water, to design and implement agricultural water operations maximizing poverty reduction impacts, and to measure results more effectively.